Party Kitchen - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created by the National Paint, Varnish, and Lacquer Association. The booklet suggests that the most successful kitchen is one built around a definitive theme. It continues to suggest various decoration possibilities with a focus on color schemes and painting projects. Provides tips and tricks for redesigning one's kitchen. Includes small stylized illustrations throughout and decorated covers. The National Paint, Oil and Varnish Association, Inc. was formed in 1933 and was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Oilseeds; Varnish and varnishing; Varnish industry; Paint industry and trade; Advertising--Paint